2015
DOI: 10.1136/neurintsurg-2014-011520
|View full text |Cite
|
Sign up to set email alerts
|

Direct aspiration first pass technique for the treatment of acute ischemic stroke: initial experience at a European stroke center

Abstract: The direct aspiration first pass technique proofed to be fast, effective, and safe. Promising revascularization results can be achieved quickly in more than 50% of patients using this technique as the firstline option. Nevertheless, stent retrievers are still warranted in approximately 40% of cases to achieve a favorable revascularization result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
81
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 23 publications
7
81
2
1
Order By: Relevance
“…18 ADAPT was implemented as described in detail previously. 4,6 Briefly, a large-bore guide catheter such as a Neuron Max 0.088 inches (Penumbra Inc, Alameda, CA) was placed distally into the internal carotid artery followed by the aspiration catheter (Penumbra ACE or ACE64) which was advanced at the thrombus surface, usually over a microcatheter and micro guidewire. Aspiration was applied, and either the clot was ingested within the catheter or was affixed at the catheter tip and withdrawn under continuous vacuum exerted by a dedicated aspiration pump.…”
Section: Endovascular Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…18 ADAPT was implemented as described in detail previously. 4,6 Briefly, a large-bore guide catheter such as a Neuron Max 0.088 inches (Penumbra Inc, Alameda, CA) was placed distally into the internal carotid artery followed by the aspiration catheter (Penumbra ACE or ACE64) which was advanced at the thrombus surface, usually over a microcatheter and micro guidewire. Aspiration was applied, and either the clot was ingested within the catheter or was affixed at the catheter tip and withdrawn under continuous vacuum exerted by a dedicated aspiration pump.…”
Section: Endovascular Proceduresmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] We aimed to identify patients in whom the aspiration component of ADAPT is most likely to be successful.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Retrospective studies have reported a high rate of revascularization (TICI 2b/3 Ͼ 90%) with the ADAPT approach, with low complication rates such as 2% embolization in a new territory and no incidence of symptomatic intracranial hemorrhage. 24,25 The imbalance of prior rtPA use, which was higher in the ADAPT group (66.1% versus 45.4% in the Solitaire group), may have impacted the rate of successful recanalization. However, the adjusted analysis for all confounding factors, including rtPA use, confirms the higher rate of recanalization in the ADAPT group.…”
Section: Discussionmentioning
confidence: 99%
“…6 Outside of clinical trials, endovascular therapy of posterior circulation strokes with stent retrievers and modern distal aspiration catheters is currently offered to a variety of patients using different selection criteria and treatment approaches, resulting in a wide range of clinical outcomes. [7][8][9][10] However, clinical and imaging predictors of success outcomes, and optimal recanalization approaches in this specific group of patients are not understood as well as in anterior circulation strokes because posterior circulation strokes have not been studied extensively. The aim of this study was to review our recent multicenter experience with endovascular treatment of …”
mentioning
confidence: 99%